Zero-dimensional plate-shaped copper halide crystals with green-yellow emissions. Issue 11 (10th May 2021) - Liu, Feng; Mondal, Debayan; Zhang, Kai; Zhang, Ying; Huang, Keke; Wang, Dayang; Yang, Wensheng; Mahadevan, Priya; Xie, Renguo
Abstract : Plate-shaped (DTA)2 Cu2 I4 crystals with green-yellow emissions, 0D structures and waveguide behavior were prepared by the employment of long alkyl chain molecules. Abstract : Low-cost and eco-friendly metal hybrid materials with zero-dimensional (0D) structures have recently attracted increasing attention owing to their excellent optical properties and wide applications. However, successful examples of 0D structural OIMHs with well-defined dimensions are still quite limited. Here, plate-shaped copper-based halide hybrids, (DTA)2 Cu2 I4, with 0D structures were successfully prepared by the employment of long alkyl chain molecules. The crystallization features were characterized by X-ray diffraction, and further investigated by theoretical simulations. The investigation on the photophysical properties indicates that 0D crystals show a broadband emission peak at ∼540 nm with a high PLQY of 60%, a long lifetime of 1.84 μs and a large Stokes shift of 210 nm under photo-excitation. The broad emission should be attributed to the self-trapping excitons as determined by the joint experiment-density functional theory studies. Also, the high optical performance and stability endow (DTA)2 Cu2 I4 with the potential for lighting phosphors by fabricating a white light-emitting diode (WLED) device. Importantly, bright PL at the edge of the plate-shaped crystal was observed, suggesting a typical waveguide behavior in a 2D system. These results validate these 2D crystals as promising luminescent materials for potential optical communication micro-devices.